Impacts of Macroeconomic Factors on Stock Returns in the Property Sector - Garnia, Erna; Rizal, Deden; Tahmat, Tahmat; Ayu Febianti Lebeharia, Auliya (KnE Social Sciences, 2022)
The objective of this research was to determine the impact of macroeconomic factors, namely the price of gold, the gross domestic product (GDP) and the money supply, on stock returns in the property sector listed on the Indonesian Stock Exchange. The data used were monthly data from 10 property stocks for the period 2013-2019. Panel data regression was used. The results indicated that the price of gold had a positive impact on returns, GDP had no impact on returns, and the money supply had a negative impact on returns. When considered together, the price of gold, GDP and money supply had an impact on stock returns in the property sector. Keywords: stock returns, macroeconomics, arbitrage pricing theory